Implementasi Hot Pack Untuk Peningkatan Suhu Tubuh Pada Pasien Hipotermi Pasca Operasi - Dzuhuri, Muh Adnan; Sukmaningtyas, Wilis; Yudha, Magenda Bisma (Yayasan Inspirasi El Burhani, 2024)
Introduction: As a kind of therapy, surgery involves cutting into the patient in order to reach the targeted location of the body. The risk of hypothermia is a potential consequence of anesthesia. A dangerous drop in core temperature, below 36 degrees Celsius, causes hypothermia. One way to alleviate cold symptoms is using a warm compress. An alternative to using hot packs to raise core temperature is a warm compress. Hot packs have many advantages over buli-buli, the most notable of which is that they can be reused and never run out of steam. Objective: This community service activity is to implement hot packs on hypothermic patients. Method: As part of their community service, volunteers take patients' temperatures using electronic thermometers. Including thirty individuals who were found to have hypothermia. Result: Impact of Volunteer Work Hypothermia after administration of a hot pack, with a pre-package average temperature of 35.20 degrees Celsius Average core temperature before administration of the hot pack: 36.50 °C Body temperature values ranged from 34.10C before implementation to 36.70C thereafter, with a low value of 35.10C and a high value of 35.90C before and after, respectively. Conclusion: This proves that there is an increase in body temperature in hypothermic patients after implementing Hot packs.